Perception of Health Care Access in Rural Georgia: Findings From a Community Health Needs Assessment Survey - Elisa Childs; Tiffany Washington (Georgia Southern University, 2022)
Background: Limited access to health care services has been cited as a barrier to care for individuals who live in rural areas, contributing to significant health disparities in this population. While perception of services has been cited as a determinant of utilization of health services, it is unknown how perception of services influences health care access in rural areas. The paucity of studies specific to areas in the United States that are medically underserved, necessitated this study and its quantification of the issues that are relevant to individuals living in rural Georgia. Methods: This study examined the perception of health care access of rural Georgians by analyzing results from a Community Health Needs Assessment survey. Multiple linear regression was performed to examine associations between perception of health care access and several environmental and sociocultural factors. Results: Two hundred and fourteen surveys were completed over a 6-week period by a largely Caucasian (85%) and female (78%) sample. Perception of health care quality was significantly related to perception of local health care access. Conclusion: Interventions and protocols that are implemented to increase health care access in rural areas should include how perception of health care quality might influence a person's understanding and consequent decision to access local health care services. Because of the ambiguous nature of how "health care quality" is defined, future research is warranted to better understand how the term is operationalized and what relationship there is between the perception of "health care quality" and health care access in a rural area.